Adverse socioeconomic position across the lifecourse increases coronary heart disease risk cumulatively: findings from the British women's heart and health study - Lawlor, D. (BMJ Group, 2005)
Objective: To examine the associations of childhood and adult measurements of socioeconomic position with coronary heart disease (CHD) risk. Methods: Cross sectional and prospective analysis of a cohort of 4286 British women who were aged 60–79 years at baseline. Among these women there were 694 prevalent cases of CHD and 182 new incident cases among 13 217 person years of follow up of women who were free of CHD at baseline. Results: All measurements of socioeconomic position were associated with increased prevalent and incident CHD in simple age adjusted models. There was a cumulative effect, on prevalent and incident CHD, of socioeconomic position across the lifecourse. This effect was not fully explained by adult CHD risk factors. The adjusted odds ratio of prevalent CHD for each additional adverse (out of 10) lifecourse socioeconomic indicator was 1.11 (95% confidence interval: 1.06, 1.16). The magnitude of the effect of lifecourse socioeconomic position was the same in women who were lifelong non-smokers as in those who had been or were smokers. Conclusion: Adverse socioeconomic position across the lifecourse increases CHD risk cumulatively and this effect is not fully explained by adult risk factors. Specifically in this cohort of women cigarette smoking does not seem to explain the association between adverse lifecourse socioeconomic position and CHD risk.